PEMETAAN SOSIAL EKONOMI UMAT ISLAM SEBAGAI DASAR PERUMUSAN STRATEGI PEMBERDAYAAN MASYARAKAT DALAM PERSPEKTIF KOMUNIKASI PEMBANGUNAN - Helfinaya Fattiyah Br. Mangunsong; Intan Safitri; Al Dira Hairani; Tasya Maulidya Hutagalung; Nadia Syahnanda; Intan Khusnul Khotimah; Riswan Rambe; Jeroh Miko (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study analyzes the significance of Muslim community socio-economic mapping as an empirical foundation for developing effective, sustainable, and transformative community empowerment strategies from a contemporary development communication perspective. Although Muslims constitute the majority population in Indonesia, they continue to experience significant socio-economic inequalities shaped by structural, historical, and institutional factors. This study employs a qualitative approach using a systematic literature review to synthesize evidence from academic publications, policy documents, and institutional reports. The findings indicate four main points. First, the socio-economic conditions of Indonesian Muslims require multidimensional mapping encompassing economic, educational, health, employment, social capital, and community aspiration aspects. Second, participatory socio-economic mapping not only generates accurate data but also functions as a development communication process that promotes critical community awareness. Third, integrating mapping results into empowerment planning produces more targeted, contextual, responsive, and sustainable programs. Fourth, the participatory development communication perspective strengthens the role of socio-economic mapping as a transformative empowerment instrument. This study proposes the Mapping-Communication-Empowerment Integration Model (I-PKP), consisting of four cyclical phases, as a conceptual framework to guide stakeholders in designing more responsive and impactful Muslim community empowerment programs.